(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Rasayana Tantra is one of the eight major divisions of Astang Ayurveda. In Ayurveda, one of the major methods of presentation of positive health has been described i.e. Rasayana. There are many activities that promote health and happiness by engendering positive emotions and experiences, which in turn promote the production of Ojas. These activities are included in Achara Rasayana . Ayurveda strongly emphasizes prevention, promotion, cure and rehabilitation. For this, it advocates to follow the principles of health, observation of principles – Dincharya (daily regimen), Ritucharya (Seasonal regimen), Ratricharya (Night routine), Sadvritta and Achar Rasayan (Ethical and Moral activities), Aahar (Food), Nidra (Sleep) and Brahmacharya (Regulated Action). Achara Rasayana is described in various texts. It means good conduct. It signifies the physical and mental conducts of a man and it has been designated as an Rasayana – a vitalizer agent for entire span of life. This is a measure having no involvement of drugs and if it is sincerely taken into practice, it may replenish and maintain total life process free from ailments. A careful analysis of qualities of Achara Rasayana reveal that most of them are related with Mana, Dhi, Dhriti along with good conduct and these results in maximum benefit. The principles of Achar Rasayana are more relevant today than ever. It goes into the heart of the issue we are trying to overcome in order to be well and healthy. Environmental toxicity and the food chain we are accustomed to have threatened our lives. The integral connection between nature and man is an understatement.